Note on Legendre numbers - R. Sitaramachandrarao; B. R. Davis (International Journal of Mathematics and Mathematical Sciences)
The definition and basic properties of Legendre Numbers are reviewed here. We then develop some new properties and identities involving sums of Legendre Numbers, including clarification of a statement in the paper of Haggard [1].